IMPLEMENTASI METODE ALGORITMA AES PADA PERLINDUNGAN DATA SISTEM LOGIN - Lie Clara; Akhmad Budi (Jurnal Informatika dan Bisnis, 2021)
At  present  the  development  of  digital  technology  and  telecommunications  is  progressing  very  rapidly throughout the world, making almost in every country always closely related to technology in their daily lives, including Indonesia. Utilization of computer applications in everyday life has become a necessity. For this reason, the issue of security and confidentiality of data and information is very important. Personal data should not be known by others to suppress the occurrence of data that is misused and used. It needs to be protected and restricted from anyone who can access important data. In this study, the authors developed a login data security system application with the AES algorithm method to assist individuals in maintaining important data, especially passwords they have. In addition this application uses a MySQL database as a means of storing data, and PHP, HTML as a programming language, and CodeIgniter as a framework for supporting system development. This  research  was  conducted  by  utilizing  the methods  in  collecting  data,  namely,  literature  study  and documentation. And utilizing the AES algorithm as a data analysis and measurement technique The design of the application that the authors propose will include a system architecture, a system description using UML diagrams, namely use case diagrams, activity diagrams, and class diagrams, there is also a design interface and program flow design to explain how the program can run and how the program displays when viewed by the user, and there is a system implementation that covers hardware specifications, installation guides, and usage guides. The cryptographic application that the authors produced through this research is intended to be able to provide a security system solution that can maintain data security on the login system so that users can stop using passwords that are weak and repetitive, so users can keep their passwords safer. Keyword : Information System, Data, Login System, AES Algorithm, Cryptography.